IMPOLITENESS IN DIGITAL POLITICAL DISCOURSE: A STUDY OF 'DIRTY VOTE' YOUTUBE COMMENTS - Putra, Kevin Permana; Widodo, Nabilah Putri; Aisyah, Almas Elmadina; Tjahyadi, Indra (JURNAL LITERASI, 2024)
Impoliteness, which deviates from social norms or respectful communication, is often seen as insulting verbal behavior. In our current era, incivility is a common occurrence in human interaction. A significant observation is the prevalence of impolite comments on social media platforms. This study identifies five forms of impoliteness: bald on record impoliteness, positive impoliteness, negative impoliteness, mimic impoliteness, and withhold impoliteness, using a practical methodology. The research focuses on deliberate instances of rudeness in the YouTube comment section. The objective is to explore imitative impoliteness in comments, along with the strategies leading to these disrespectful remarks. Culpeper’s (1996) theory is applied, concentrating on a single YouTube account, Dirty Vote, which caused controversy in Indonesia in 2024. The study employs a qualitative descriptive method, analyzing data from previously collected information. The comments section of various videos uploaded by Dirty Vote serves as the study's object, providing an in-depth examination of impoliteness.